Flow regime characterization of a silicon-based vaporizing liquid microthruster. (April 2022) - Fontanarosa, D.; Francioso, L.; De Giorgi, M.G.; De Pascali, C.; Ficarella, A.; Vetrano, M.R.
Abstract: The present work discusses an experimental investigation of the flow into a silicon-based vaporizing liquid microthruster equipped with sensing capabilities and low-power on-channel secondary heaters. The sensing capabilities (resistance temperature detectors and capacitive void fraction sensors) are used to investigate the flow instability and to evaluate its performances. The device has a sandwich structure composed of a silicon substrate and a glass substrate. This last one allows optical access into the device. The main heating of the propellant is provided using a platinum resistive heater placed on the bottom of the silicon layer. By varying the electrical power supplied to the main heater at fixed mass flow rate, three flow regimes have been observed and investigated: fully liquid flow, two-phase flow, and fully vaporized flow. Their dynamics have been captured through high-speed micro-flow visualizations under rough vacuum conditions (about 29 kPa). Furthermore, the expansion of the exhaust vapor plume exiting from the micronozzle has been analyzed via Schlieren visualizations. Results highlighted the occurrence of a cyclic flow behavior during the two-phase flow regime. In contrast, the flow exhibits the presence of both liquid and vapor phases at the micronozzle exit. Once the fully vaporized flow regime is established, the two-phase flow dynamics into the inlet chamber become more stable with complete filling and more uniform distribution of the flow at the microchannels entrance. Schlieren imaging captured the increase of the exhaust plume spreading half-angle when moving from ambient condition towards rough vacuum. Highlights: The flow topology is investigated during different VLM's regimes. An electro-thermal cycle is observed during VLM functioning. Thrust plume Schlieren Imaging is performed in rough vacuum conditions.